The distribution and conservation of Gurney's Pitta Pitta gurneyi in Myanmar. Issue 3 (September 2014) - DONALD, PAUL F.; HLA, HTIN; WIN, LAY; AUNG, THIRI DAWEI; MOSES, SAW; ZAW, SAO MYO; AG, TIN TUN; OO, KYAW NAING; EAMES, JONATHAN C.
Summary Following a recent assessment of the distribution and habitat use of Gurney's Pitta in Myanmar (Burma), further extensive surveys were undertaken in 2010, 2011 and 2012. These have extended the species' known altitudinal limit to between 250 m and 300 m asl and its latitudinal limit to above 12.5°N, around 80 km north of the northernmost historical record, although the species was recorded far less frequently at higher altitudes and latitudes. Birds were recorded in a range of forested habitats, from intact primary forest to secondary and bamboo forest, with no significant difference between major forest types in the likelihood of occurrence. Niche envelope modelling (MaxEnt) suggested a total range size in Myanmar of 3, 379 km2, and did not identify any potentially suitable areas in adjacent parts of Thailand. The species' preference for warmer, wetter areas on flat ground, conditions ideal for growing oil palm and rubber, suggest that its distribution is likely to contract in the near future. The entire range of Gurney's Pitta in Myanmar falls within the part of the country most suitable for commercial oil palm production, although the projected yields within its range are low to moderate. Field surveys found evidence of rapid recent deforestation and high levels of hunting and trapping in many parts of the region. The species' range in Myanmar does not overlap with any protected areas. The protection of southern Myanmar's biodiversity will require substantial investment by foreign conservation interests, sympathetic land-use planning and the strengthening of environment legislation. Protection of extensive tracts of lowland forest within the range of Gurney's Pitta, particularly the proposed Lenya National Park and the adjacent Ngawun and Htaung Pru Reserve Forests, is urgently needed. Conserving these areas will also protect populations of other globally threatened bird and mammal species.